Attention Deficit Hyperactivity Disorder in the Light of the Epigenetic Paradigm - Schuch, Viviane; Utsumi, Daniel Augusto; Costa, Thaís Virgínia Moura Machado; Kulikowski, Leslie Domenici; Muszkat, Mauro (Frontiers in Psychiatry, 2015)
Attention deficit hyperactivity disorder (ADHD) is a highly prevalent neurodevelopmental disorder characterized by a definite behavioral pattern that might lead to performance problems in the social, educational or work environments. In the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-V), the symptoms of ADHD were restricted to those associated with cognitive (attention deficit) and behavioral (hyperactivity/impulsivity) deficits, while deficient emotional self-regulation (DESR), a relevant source of morbidity, was left out. The etiology of it is complex, as its exact causes have not yet been fully elucidated. ADHD seems to arise from a combination of various genetic and environmental factors that alter the developing brain, resulting in structural and functional abnormalities. The aim of this paper was to review epigenetics and ADHD focused on how multidimensional mechanisms influence the behavioral phenotype.